Successes and failures of peacekeeping operations: A case study on The United Nations Organization Stabilization Mission in the Democratic Republic of Congo (MONUSCO) - Shıkwambane, Parausia Tlhlompho (İstanbul Sabahattin Zaim Üniversitesi, 2022)
The study analyses the effectiveness of the United Nations Peacekeeping Operation in the Democratic Republic of Congo (DRC). The DRC has been troubled by two civil wars since the 1990s. And the United Nations (UN) peacekeeping mission has been actively involved in trying to maintain peace in the DRC. However, contemporary events and the history of the DRC are constant reminders that violence remains dominant and continues to impede the institutional, social, and economic development of the country. The Congo conflict is one of the most complex in Africa and the most active in the world today. To achieve peace, security, and stability and resolve the crisis in the country, the UN deployed MONUSCO peacekeeping operation. Here, effectiveness becomes instrumental in analysing the successes and failures of the peacekeeping operation and determining its outcome. The study utilises Darya Pushkina's four indicators to measure the effectiveness of peacekeeping in the Congo: Limitation of Violence, Reducing Human Suffering, Preventing Spillovers and the Promotion of Conflict Resolution. Therefore, the study investigates how the United Nations peacekeeping operation in the country has evolved and explores the challenges that peacekeeping in the DRC encounters. And it examines the factors that contribute to the successes and failures of MONUSCO in the DRC. The study suggests that the United Nations has been instrumental in achieving small achievements but has not been effective in all areas.

Çalışma, Kongo Demokratik Cumhuriyeti'ndeki (KDC) Birleşmiş Milletler Barış Gücü Operasyonu'nun etkinliğini analiz ediyor. KDC'de 1990'lardan bu yana iki iç savaştan mustariptir ve Birleşmiş Milletler (BM) barış misyonu, KDC'de barışın korunmasına aktif olarak katılmıştır. Bununla birlikte, KDC'nin tarihi ve günümüzdeki gelişmeler, ülkede şiddetin baskın olmaya devam ettiğini ve ülkenin kurumsal, sosyal ve ekonomik gelişimini engellemeye devam ettiğinin göstermektedir. Kongo çatışması, Afrika'nın en karmaşık ve bugün dünyanın en aktif çatışmalarından biridir. BM, barış, güvenlik ve istikrarı sağlamak ve ülkedeki krizi çözmek için MONUSCO barış operasyonunu devreye geçirmiştir. Bu bağlamda operasyonun etkinliğini, başarısını ve başarısızlığını analiz etmek önem arz etmektedir. Çalışma, Kongo'da barışı korumanın etkinliğini ölçmek için Darya Puşkina'nın dört göstergesini kullanmaktadır: Şiddetin Sınırlandırılması, İnsan Acılarının Azaltılması, Dağılmaların Önlenmesi ve Çatışma Çözümünün Desteklenmesi. Bu nedenle, çalışma ülkedeki BM barış operasyonunun nasıl geliştiğini ve KDC'de barışı korumanın karşılaştığı zorlukları araştırmaktadır. Ve MONUSCO'nun KDC'deki başarılarına ve başarısızlıklarına katkıda bulunan faktörleri incelemektedir. Çalışma, BM'nin küçük başarılar elde etmede etkili olduğunu ancak her alanda etkili olmadığını göstermektedir.
Barışı koruma operasyonlarının başarısı ve başarısızlığı: Kongo Demokratik Cumhuriyeti Birleşmiş Milletler Örgütü istikrar misyonu (MONUSCO) üzerine bir örnek olay incelemesi
Keywords: Democratic Republic of Congo; Successes and Failures; United Nations; MONUSCO; Peacekeeping and Conflict; Demokratik Kongo Cumhuriyeti; Başarı ve Başarısızlık; Birleşmiş Milletler; MONUSCO; Barış Gücü ve Çatışma